2017
DOI: 10.1128/jvi.01514-16
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Inducible Oligoadenylate Synthetase-Like Protein Acts as an Antiviral Effector against Classical Swine Fever Virus via the MDA5-Mediated Type I Interferon-Signaling Pathway

Abstract: Classical swine fever virus (CSFV) is the causative agent of classical swine fever (CSF), which poses a serious threat to the global pig industry. Interferons (IFNs) and IFN-stimulated genes (ISGs) play a key role in host antiviral defense. We have previously screened the porcine 2′-5′-oligoadenylate synthetase-like protein (pOASL) as a potential anti-CSFV ISG using a reporter CSFV. This study aimed to clarify the underlying antiviral mechanism of pOASL against CSFV. We confirmed that CSFV replication was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 43 publications
(70 reference statements)
1
37
0
Order By: Relevance
“…To further verify that MERTK antagonizes the host innate immune response to CSFV, we quantified the mRNA levels of IFN-β and suppressor of cytokine signalling protein 1 (SOCS1) in MERTK-knockdown cells infected with CSFV at 24 hpi. Our results showed that silencing of MERTK resulted in increased mRNA levels of IFN-β and SOCS1, as well as of GBP1 and OASL ( Figure 6E), which have been identified as potent anti-CSFV interferon-stimulated genes (ISGs) [27,40]. Taken together, these findings suggest that MERTK facilitates CSFV entry and enhances viral replication.…”
Section: Mertk Antagonizes Type I Ifn Signalling Pathway In Csfv Infementioning
confidence: 58%
See 1 more Smart Citation
“…To further verify that MERTK antagonizes the host innate immune response to CSFV, we quantified the mRNA levels of IFN-β and suppressor of cytokine signalling protein 1 (SOCS1) in MERTK-knockdown cells infected with CSFV at 24 hpi. Our results showed that silencing of MERTK resulted in increased mRNA levels of IFN-β and SOCS1, as well as of GBP1 and OASL ( Figure 6E), which have been identified as potent anti-CSFV interferon-stimulated genes (ISGs) [27,40]. Taken together, these findings suggest that MERTK facilitates CSFV entry and enhances viral replication.…”
Section: Mertk Antagonizes Type I Ifn Signalling Pathway In Csfv Infementioning
confidence: 58%
“…Genomic RNA copies of CSFV were quantified by realtime RT-PCR (RT-qPCR) as previously described [27].…”
Section: Real-time Rt-pcrmentioning
confidence: 99%
“…The expression of many ISGs is induced following type I IFN treatment. However, some of them exert independent antiviral functions that may affect CSFV replication [6,7,9]. This knowledge helps to explain why knockdown of ISG15 notably enhanced CSFV replication but did not totally neutralize the anti-CSFV activity of IFN-α ( Figures 2D, E).…”
Section: Discussionmentioning
confidence: 88%
“…RNA viruses of the family Flaviviridae are sensitive to type I IFN, and replication of CSFV is attenuated by treatment with IFN-α [5]. Although many studies have focused on screening and identifying antiviral ISGs and elucidating their antiviral mechanisms, only 2′,5′-oligoadenylate synthetase-like protein (OASL), myxovirus resistance protein 1 (Mx1), viperin, guanylate-binding protein 1 (GBP1), and IFN-inducible transmembrane proteins (IFITMs) have been identified to inhibit CSFV infection or replication [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…After being activated, OAS promotes the synthesis of 2-5 oligoadenylate, which activates RNase L. Upon binding 2′-5′-linked oligoadenylates (2-5 A), activated RNase L degrades cellular and viral RNA 34 . This RNase L-dependent pathway is best characterized; however, recent studies have described OAS antiviral activity through a RNase L-independent pathway 35,36 . In chickens, OAS has been shown to be encoded by only one gene (OASL) 37 and to be upregulated after infection with different viruses 38,39 including NDV 3,4,21 .…”
Section: Discussionmentioning
confidence: 99%